PTPN11 mutations in LEOPARD syndrome. Issue 8 (1st August 2002) - Legius, E; Schrander-Stumpel, C; Schollen, E; Pulles-Heintzberger, C; Gewillig, M; Fryns, J-P
Abstract : LEOPARD syndrome is an autosomal dominant disorder with multiple lentigines, congenital cardiac abnormalities, ocular hypertelorism, and retardation of growth. Deafness and genital abnormalities are less frequently found. We report a father and daughter and a third, unrelated patient with LEOPARD syndrome. Recently, missense mutations in the PTPN11 gene located in 12q24 were found to cause Noonan syndrome. All three cases of LEOPARD syndrome reported here have a Y279C mutation in the PTPN11 gene. We hypothesise that some PTPN11 mutations are associated with the typical Noonan syndrome phenotype and that other mutations, such as the Y279C mutation reported here, are associated with both the Noonan syndrome phenotype and with skin pigmentation anomalies, such as multiple lentigines or café au lait spots.